Model Sistem Digitalisasi Dokumen Akreditasi untuk Mendukung Proses Validasi Oleh Asesor Menggunakan Metode Ekstraksi Transformasi dan Load - Setiyadi, Angga; Dwiguna Sumitra, Irfan; Hardyanto, Chrismika; Reza, Donny (Program Studi Teknik Informatika - Universitas Komputer Indonesia (UNIKOM), 2025)
This research aims to develop a university accreditation document digitization system that facilitates the validation process by assessors and increases efficiency, transparency, and security in document management. The developed system integrates a web-based Extract, Transform, and Load (ETL) process for accreditation data, starting with uploading Excel files to Google Drive, data extraction by the admin, and data transformation for structured structuring. Test results show that the digital system is able to accelerate processing time per document from 180 seconds to 45 seconds (a 75% improvement), accelerate document title searches from 90 seconds to 10 seconds (an 88.9% improvement), and increase data accuracy from 92% to 99% (+7 percentage points). These improvements were achieved through the implementation of automated searches, standardized data formats, and automatic validation before loading data into the database. The implementation of the Extract, Transform, and Load system has been proven to minimize manual errors, increase speed, and improve the accuracy and regularity of accreditation data, making it a representative solution for modern and standardized education data management.